Influence of the Principles Academic Supervision on Educators Work Professionalism in ES Pembangunan UNP - Febrianti, Helsi; Nella, Nella; Gazali, Hamdani; Rifma, Rifma; Marsidin, Sufyarma (Postgraduate School, Universitas Negeri Padang, 2023)
This study aims to analyze the effect of the principal's academic supervision on the professionalism of teacher teachers. This research is a qualitative type of research using library research or library research, namely by taking data sources from books, journals, and other written works related to the topics discussed. The results of the literature study that has been carried out will be analyzed and described in the results and discussion section. Based on the discussion above, it can be concluded that the implementation of academic supervision by the school principal on the professionalism of teacher work is very influential and related. Supervision activities by the school principal are ongoing coaching and assistance activities to assist teachers and other staff in overcoming educational problems so that teachers and other staff feel confident in improving the performance and quality of education.